An Analysis of Stylistic in After Dark by Haruki Murakami - Kuni Fauziyati; Sulistyaningsih (JournEEL, 2020)
Haruki Murakami features some unique stylistic. One of the reasons could be the voluminous nature of a novel to apply stylistic analysis. However, if it is applied on a novel, one can better understand and enjoy the different styles used in a certain novel in addition to arousing curiosity for more studies. Not only arouse curiosity, according to some recent researches, stylistic analysis could serve as the best way to learning English as a foreign language for a pedagogy purpose. This article limits itsself to stylistic analysis of After Dark by Haruki Murakami. This novel contains 18 chapters and because of time constrains. this article will focus on selected chapters that are considered to be stylistically representative in the novel. Existing methods might be able to formulate ideas and thoughts based on scientific approaches. This study used literary stylistic analysis as the actual approach. Literary stylistic analysis was selected because it gave an apportunity to intergret linguistic description with critical interpretation. Based on the results of the analysis carried out on After Dark by Haruki Murakami, it can be concluded that the novel consists of figurative languange and syntactic language.